Partial Splenic Artery Embolization for Idiopathic Warm Autoimmune Hemolytic Anemia Refractory to Medical Therapy - Mohamad Omar Hadied; Riyad Yazan Kherallah; Mariam Salman; Khalid Eteer; Scott Schwartz (The Arab Journal of Interventional Radiology)
Purpose: While Partial Splenic Artery Embolization (PSAE) is a useful procedure that has been performed for a variety of indications including trauma and hypersplenism, it has only been rarely described as a treatment for Idiopathic Warm Autoimmune Hemolytic Anemia. Previous reports in the literature are limited to case reports in situations that include the patient being a poor surgical candidate, the inability to transfuse blood during surgery because of autoantibodies, and a patient's refusal of blood products on religious grounds. Materials and Methods: A case report describing the case of a 27-year-old male diagnosed with idiopathic warm Autoimmune Hemolytic Anemia treated successfully with partial splenic artery embolization (PSAE) as a bridging therapy to definitive surgical splenectomy. Results: The patient's pre-procedure hemoglobin was 2.1 g/dl. The first hemoglobin post-procedure was 4.5 g/dl. After embolization, the patient remained in the inpatient setting for eight days for close observation. During the inpatient hospitalization the patient's hemoglobin continued to trend upwards until it stabilized around 6 g/dl. Inpatient laboratory workup also showed increasing haptoglobin, and decreasing LDH. After discharge, the patient developed persistent pain two months post-procedure. An elective splenectomy was scheduled three months after the embolization procedure to address the persistent pain. Six months' post embolization procedure and three months postoperatively, the patient is doing well clinically with a hemoglobin of 14 g/dl. Conclusion: In conclusion, this case demonstrates the utility of a Partial Splenic Artery Embolization (PSAE) as an acute life-saving intervention for poor surgical candidates with idiopathic warm Autoimmune Hemolytic Anemia (AIHA) refractory to medical therapy.